Identifying, treating, and preventing childhood trauma in rural communities - Baker, Marion A.; Ford, Jacqueline; Canfield, Brittany; Grabb, Traci; IGI eBooks; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, PA 17033, USA) : IGI Global, 2016)
"This book depicts the issues and challenges rural areas face when treating victims of trauma, especially children and adolescents by featuring information on language and cultural barriers, as well as the lack of resources available within these rustic environments"--Provided by publisher.
Psychosocial aspects of trauma and related disorders / Firdous War -- Child maltreatment prevention in rural communities / Tosin O. Alabi, Sandra D. Barnes -- The impact of parental substance abuse on children / Anu Dandona -- Does location matter?: the impact of family violence in rural areas / Samar Adi -- Treating child sexual abuse in rural communities / Leah Genieve Kenyon-George -- School violence among children and adolescents in rural communities / Michelle F. Wright -- When the system fails: challenges of child trauma on adoptive families' social and emotional system / Jacqueline Y. Ford -- Assessment of childhood trauma in rural settings / Apryl A. Alexander, Megan E. Harrelson -- What if a whole community came together?: collaborating to ensure no wrong door to services / Rebecca Hoffmann Frances -- Spirituality: a path to healing for children in rural communities / Sandra D. Barnes, Tosin O. Alabi -- "Rural-specific" types of childhood trauma in rural communities / Roberto Jose Velasquez, Yadira Juarez -- Clinical forensic issues in child trauma stemming from juvenile fire setting and bomb making: culturally responsive risk assessment and treatment paradigm for rural settings / Ronn Johnson [and 4 others] -- Childhood trauma and barriers in a rural setting: my experience with childhood trauma and barriers in a rural setting / Sonja Lee Salcido -- The contagion of trauma: exploring attachment through the book love lessons / James Dumesnil.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 06/18/2016).
Keywords: Rural children -- Mental health -- United States; Child mental health services -- United States; Psychic trauma in children -- United States; Child welfare -- United States; Child Health Services; Psychological Trauma -- therapy; Mental Health Services; Rural Health Services; United States; Child abuse; Child neglect; Domestic violence; Psychopharmacology; Substance abuse; Trauma informed care; Electronic books